Gulf Cooperation Council (GCC) : Labor Market Reforms to Boost Employment and Productivity in the GCC. (Policy Papers; Policy Paper ;, 2013)
The GCC growth model has delivered substantial improvements in living standards over several decades. Access to foreign labor has supported rapid growth in the non-oil sector and price stability in the region. It has also resulted in positive spillovers to the migrant-sending countries through large remittance flows. At the same time, governments have increased public-sector employment and have helped raise standards of living. However, the growth model has involved costs: the public-sector wage bill is relatively high, there is limited employment of nationals in the private sector, labor productivity has declined or stagnated, and there is limited progress on economic diversification.